Variability of competition performance in throwing and jumping events in elite athletes - Woo, B. H.; Zatsiorsky, V. M. (Human Movement, 2006)
Purpose. This study addresses the following questions: (1) What is the magnitude of the trial-to-trial variability in elite athletes? (2) What is the effect of the performance level on the performance variability? (3) Is the performance dependability (the percentage of successful trials) affected by the performance level? Basic procedures. Official protocols of competitions in throwing and horizontal jumps were retrieved via the Internet using the Google as the search engine. The competitions included Olympic Games, World Championships, regional competitions, such as European Championships, etc. The competition protocols of 4602 athletes were analyzed. The magnitudes of the trial-to-trial variability (ranges, standard deviations and coefficients of variation) were determined. Main findings. The performance variability: (a) was slightly larger in the best athletes; (b) was larger in female athletes than in males in all events; and (c) was larger in `long` throwing events (discus, hammer and javelin) than in horizontal jumps and shot putting (p < 0.01). With the improvement of the performance level, the percentage of the successful attempts increased. Conclusions. With the improvement in the performance level the dependability of the athlete`s performance improves, while the performance variability does not change.